PROBLEMS AND PRIORITIES OF DEVELOPMENT OF DOMESTIC NANOINDUSTRY - Olga B. Lomakina (Модернизация, инновация, развитие)
Russia has a powerful groundwork in the field of nanotech. All prerequisites  are available in the country necessary to form an uptodate NIS. However the system of implementing innovation processes in the field of nanotechnologies and in the management of this branch of industry remains lowefficient.